1993
DOI: 10.1007/bf00735368
|View full text |Cite
|
Sign up to set email alerts
|

The ion channel of muscle and electric organ acetylcholine receptors: Differing affinities for noncompetitive inhibitors

Abstract: 1. Muscle and electric organ acetylcholine receptors (AChR's) were expressed in Xenopus laevis oocytes and differential effects of noncompetitive blockers on each type of receptor were analyzed using a two-electrode voltage clamp. 2. The positively charged channel blockers, phencyclidine (PCP) and tetracaine, displayed a much lower potency on muscle receptor than on the electric organ receptor. The IC50 for both blockers at the electrocyte receptor was close to 1 microM at -60 mV and even lower at more hyperpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…Since PCP potency is not decreased by membrane depolarization, the binding site of PCP is not in the ion channel of BC 3 H-1 receptors. This contrasts with previous observations of voltage dependence of PCP with the electric organ receptor (Eterovic, et al, 1993b) suggesting that PCP may bind to different sites in these two receptors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Since PCP potency is not decreased by membrane depolarization, the binding site of PCP is not in the ion channel of BC 3 H-1 receptors. This contrasts with previous observations of voltage dependence of PCP with the electric organ receptor (Eterovic, et al, 1993b) suggesting that PCP may bind to different sites in these two receptors.…”
Section: Discussioncontrasting
confidence: 99%
“…Using single-channel recordings from muscle cells (Changeux et al, 1986;Oswald, 1986, 1989) and two-electrode voltage-clamp from oocytes expressing BC 3 H-1 nAChRs (Eterovic et al, 1993b), it has been observed previously that PCP inhibits ACh-induced currents in a bimodal maner; low and high, but not intermediate concentrations of PCP inhibit the receptor. Furthermore, PCP inhibits the AChR from Torpedo electric organ with higher potency than mouse muscle AChR.…”
mentioning
confidence: 99%
“…The different results may be due to molecular differences in the M2 region between frog and mouse muscle AChRs, 34 similar to the difference in affinity to phencyclidine between AChRs from Torpedo electric organ and mouse muscle; which is based on a difference in three amino acids within the ionic channel. 35 It has been reported that ACh potentials in rat soleus muscle fibers are potentiated with 1 M imipramine. 25 However, under our experimental conditions even smaller concentrations of imipramine exerted an inhibitory effect on the ACh-current.…”
Section: Discussionmentioning
confidence: 99%
“…Considering this feature, we used MINDO3 method to compute equilibrium geometry and electronic structure of clonidine molecule and molecules of three typical LA: 2-(ethylpropylamino)-2',6'-butyroxylidide (etidocaine), procaine, and tetracaine. A certain similarity in the spatial structure of the examined molecules was revealed.In addition to the blocking action on the potentialoperated ionic channels, many LA modify firing of neurons and skeletal and cardiac muscle cells by inhibiting the nicotinic receptor-channel complex [5,6]. This inhibitory effect (IC 50 ) varied form 1 to 70 µM [9].…”
mentioning
confidence: 99%
“…In addition to the blocking action on the potentialoperated ionic channels, many LA modify firing of neurons and skeletal and cardiac muscle cells by inhibiting the nicotinic receptor-channel complex [5,6]. This inhibitory effect (IC 50 ) varied form 1 to 70 µM [9].…”
mentioning
confidence: 99%